Religious Moderation Reflected on Students' Digital Comic: A Speech Act Analysis - Fourica Yanottama; Andhika Optara Kusuma; Aris Hidayatulloh (International Journal of English Learning and Applied Linguistics (IJELAL), 2023)
This study discusses speech acts in Digital Comic discourse created by UIN Raden Mas Said Surakarta students who are members of the Creative Digital Skills Development Class. The comic discourse campaigns for the importance of tolerance both from religion and fellow human beings. By using Searle's theory, analysis of speech acts in discourse is carried out. Searle provides further categories of illocutionary speech acts into representative, directive, commissive, expressive, and declarative categories. These categories make it easier for researchers to see the specific meaning in question. The data from this study emphasize the utterances uttered by the main comic characters. In addition, images from data become secondary data from this study because discourse consists of two units, namely text (verbal) and images (non-verbal). The data is processed and classified into several speech act classifications proposed by Searle. Data is described by qualitative methods. The results of this study indicate that the speech acts reflected from digital comics by UIN Raden Mas Said Surakarta students have topics that refer to tolerance and maintaining harmony between religious communities or among people. From the 15 data, there are directive, expressive, and representative speech acts with dominant directive speech acts. The results show that the use of directive speech acts is the main and most effective reference in conveying the moral message of invitation, namely the invitation to maintain harmony. While expressive speech acts are used as speech acts that reflect empathy for others. In this case, it is the empathy between friends or religion.